Metabolomics markers in Neurology: current knowledge and future perspectives for therapeutic targeting. (2nd July 2020) - Bonomo, Roberta; Cavaletti, Guido; Skene, Debra J.
ABSTRACT: Introduction: Metabolomics is an emerging approach providing new insights into the metabolic changes and underlying mechanisms involved in the pathogenesis of neurological disorders. Areas covered: Here, the authors present an overview of the current knowledge of metabolic profiling (metabolomics) to provide critical insight on the role of biochemical markers and metabolic alterations in neurological diseases. Expert opinion: Elucidation of characteristic metabolic alterations in neurological disorders is crucial for a better understanding of their pathogenesis, and for identifying potential biomarkers and drug targets. Nevertheless, discrepancies in diagnostic criteria, sample handling protocols, and analytical methods still affect the generalizability of current study results.